2018
DOI: 10.1194/jlr.m080374
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase promotes mitochondrial dysfunction due to glutamate-induced regulated necrosis

Abstract: Inhibiting the glutamate/cystine antiporter system x, a key antioxidant defense machinery in the CNS, could trigger a novel form of regulated necrotic cell death, ferroptosis. The underlying mechanisms of system x-dependent cell demise were elucidated using primary oligodendrocytes (OLs) treated with glutamate to block system x function. Pharmacological analysis revealed ferroptosis as a major contributing factor to glutamate-initiated OL death. A sphingolipid profile showed elevations of ceramide species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 85 publications
(122 reference statements)
4
62
0
Order By: Relevance
“…We suggest that cooperative cytotoxicity be considered among mechanisms of inter-species communication, providing enhanced ability to damage host tissue, increase inflammation, and introduce specific metabolic products associated with harm to humans. For example, ceramide (exposed on target cell membranes when sphingomyelin is hydrolyzed) is associated with an increasing range of physiological harm, including to mitochondrial function [16], and is recognized in the pathogenesis of Parkinsonism [17]. Oxidized sterols, a product of the sequential action of phospholipase and cholesterol oxidase have long been implicated in complex cardiovascular pathology [18].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that cooperative cytotoxicity be considered among mechanisms of inter-species communication, providing enhanced ability to damage host tissue, increase inflammation, and introduce specific metabolic products associated with harm to humans. For example, ceramide (exposed on target cell membranes when sphingomyelin is hydrolyzed) is associated with an increasing range of physiological harm, including to mitochondrial function [16], and is recognized in the pathogenesis of Parkinsonism [17]. Oxidized sterols, a product of the sequential action of phospholipase and cholesterol oxidase have long been implicated in complex cardiovascular pathology [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another major pathway of sphingolipid metabolism starts with SM hydrolysis and is catalyzed by a sphingomyelinase family enzymes, ASM and NSM, yielding phosphorylcholine and ceramide (47). Hydrophobic ceramide is further hydrolyzed by ceramidase to form more hydrophilic sphingosine, which could leave the intracellular compartment, where it is generated to reach mitochondria (21,23,24). ASM is encoded by the Smpd1 gene and translated into 629 amino acid proprotein, which, because of differential modification and trafficking processes, gives rise to two distinct isoforms, lysosomal and secretory ASM (48).…”
Section: Tbi Triggered Asm Activation Via Posttranscriptional Mechanismsmentioning
confidence: 99%
“…It has been shown that a partial suppression of COX activity by cyanide increases mitochondrial ROS formation (53). Moreover, sphingosine-mediated modest inhibition of COX activity enhanced mitochondrial ROS emission in situ (24,52), which might contribute to oxidative stress, causing an imbalance between oxidant and antioxidant agents in the injured brain (54). Enhanced production of ROS could cause oxidative/nitrosative stress, leading to damage in lipids, proteins, and nucleic acids, known to occur in TBI (55).…”
Section: Tbi-induced Mitochondrial Dysfunction Is Rescued In Asm-defimentioning
confidence: 99%
See 2 more Smart Citations